IMPLEMENTATION OF JAPANDI CONCEPT AT WISMA MULIA NURSING HOME WEST JAKARTA - Rizki, Alfia (Arty: Jurnal Seni Rupa, 2022)
When a person has aged, his life is no longer full of energy and slowly begins to get a decline in body functions. This has resulted in the need for support for good and comfortable housing facilities, one of which is an Nursing Home. The elderly home, which is commonly known as Panti Werdha, is a residential facility for the elderly. In this study, we will take the object of an elderly home named Panti Werdha Wisma Mulia. The author will carry the Japanese Scandinavian concept or better known as Japandi at the Wisma Mulia Nursing Home. Apart from following the concepts that developed according to the times, the selection of the Japandi concept was able to provide a comfortable atmosphere for the elderly. This is because the Japandi concept prioritizes minimalism and warmth on the design side. So that it can create a warm, quiet, spacious room atmosphere, and of course provide a comfortable and safe effect for the elderly who inhabit it. The research was conducted by direct observation at the orphanage to obtain building data, residents' habits and photos of the room's atmosphere, as well as looking for data and building precedents with the Japanese concept. Furthermore, the author will redesign the design of the Wisma Mulia Nursing Home by implementing the Japandi concept. The result is an image of an interior design perspective as well as an explanation and benefit of the design. The author hopes that the design can be useful if it is realized and provides comfort for the elderly.